STUDI EKSPLORASI PENGARUH KONTEN KEKERASAN DALAM VIDEO GAME DAN TENDENSI AGRESI PADA SISWA SMA DI KOTA BATAM - Hendi Sama; Jecky Fransisco (UNIVERSITAS STEKOM, 2023)
This study aims to analyze the effect of violent content in video games related to situational factors and personal factors consisting of gender, age, aggression motivation, and aggressive personality and whether it influences aggressive behavior based on the General Aggression Model (GAM). This study has used quantitative and qualitative methods with a sampling technique that is random-stratified-proportional with the target being high school students in Batam city. In the quantitative method, as many as 400 respondents were obtained while in the qualitative method there were 30 respondents. The data analysis method used begins with a data quality test, namely the outlier test, validity test, and reliability test, then the regression test consists of the normality test, F test, T test, multicollinearity test, heteroscedasticity test, R and R2 test. The results of this study have shown that in the quantitative method the motivational factors of aggression and aggressive personality affect aggressive behavior while the results obtained from the qualitative method only that motivational factors of aggression influence aggressive behavior.